Suppose f(x) = x2 and g(x) = 2x − 3. What is the value of g(4) + f(−3)?

Question

Suppose f(x) = x2 and g(x) = 2x − 3. What is the value of g(4) + f(−3)?

0

Answers ( No )

    0
    2021-11-23T18:09:56+00:00

    In order to find the value of g(4)+f(-3), we must substitute those values into the functions first.

    Substitute -3 into f(x).

    f(x)=x²

    f(-3)=(-3)²

    f(-3)=9

    Substitute 4 into g(x).

    g(x)=2x-3

    g(4)=2(4)-3

    Using the rules of PEMDAS, multiply first then subtract.

    g(4)=8-3

    g(4)=5

    Therefore, if f(-3) is 9 and g(4) is 5, we must add the two values together.

    5+9=14

    The value of g(4)+f(-3) is 14.

Leave an answer

Browse
Browse